Green wireless network optimisation strategies within smart grid environments for Long Term Evolution (LTE) cellular networks in Malaysia. (January 2016) - Alsharif, Mohammed H.; Nordin, Rosdiadee; Ismail, Mahamod
Abstract: This study investigated the possibility of integrating a renewable energy system with an existing energy source (electricity grid) to supply mobile base stations in the on-grid sites of Malaysia and minimise the annual Operational expenditure (OPEX). Based on the available renewable energy resources in Malaysia, three options for this goal were examined: (i) photovoltaic/electric grid, (ii) wind energy/electric grid, and (iii) photovoltaic/wind energy/electric grid. System simulations were performed with the software HOMER, using wind speed, solar irradiance, load demand, component costs and technical specifications as well as various minimum renewable fraction (MRF) values. Three key aspects were analysed: (i) energy yields, (ii) economics, and (iii) greenhouse gas (GHG) emissions. The findings herein demonstrate that the hybrid photovoltaic/wind energy/electric grid power system delivered the highest energy to the load of the renewable energy system (48.91%), which reduces both the operating costs and pollution rate. Whereas, cost of the project is large compared with the photovoltaic/electric grid power system. However, large benefits for mobile operators in terms of OPEX reduction can be achieved. The average annual OPEX savings of the hybrid wind energy system was the lowest at 30%, whereas that of the hybrid solar system was 35% and that of the hybrid photovoltaic/wind energy/electric grid was as high as 39%. Highlights: Investigated the possibility of integrating a photovoltaic/electric grid. Investigated the possibility of integrating a wind energy/electric grid. Investigated the possibility of integrating a photovoltaic/wind energy/electric grid. System simulations were performed with the software HOMER.